On the transient radiation of energy from simple current distributions and linear antennas. - Smith, Glenn S. (IEEE Antennas & propagation magazine.)
Smith (1998) examined the radiation from two simple filamentary current distributions: traveling-wave and uniform. The radiated or far-zone electric field was computed for an excitation that was a Gaussian pulse in time. Two interpretations for the origin of the radiation were presented, based on the far-field results. The present article continues this investigation; however, the emphasis is on an examination of the near field and the related transport of energy away from the current filament. We examine traveling-wave and standing-wave current distributions, because these distributions are frequently used to model practical antennas. Exact analytical expressions are presented for the electric and magnetic fields of the assumed, filamentary current distributions when the excitation is a general function of time. For the filamentary distributions, the current and charge are confined to a line (a line source). There is no radius associated with the filament. The expressions for the fields apply in both the near and far zones, and are used to determine the Poynting vector. For an excitation that is a Gaussian pulse in time, exact analytical expressions are obtained for the energy leaving the filament per unit time per unit length, the total energy leaving the filament per unit length, and the total energy radiated. Graphical results based on these expressions are used to study the energy transport from the filamentary current distributions. The results for the standing-wave current distribution are compared with those from an accurate analysis of a pulse-excited, cylindrical monopole antenna, performed using the FDTD method.